11. THE CURRENT STATUS OF INTERNAL MEDICINE MEDICAL NURSING RECORD KEEPING AND SOME RELATED FACTORS AT HANOI TAM ANH GENERAL HOSPITAL 2022 – 2023 (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the status of compliance with medical nursing records and analyze some factors related to the quality of nursing records.Subjects and research methods: The Cross-sectional description study of 240 medical nursing recordeds at Tam Anh General Hospital from 12/2022 to 04/2023.Results: The current state of medical nursing records meeting 85% total nursing record score is 95.8%; those meeting 100% total nursing record score is 17.9%. The rate of successful recording of the patient’s initial assessment form (87.9%), monitoring the patient’s progress and care plan (54.2%), the fall risk assessment sheet (80%), the health advice and education sheet (47.9%), administration and disclosure of medication sheet for patients (73.8%), monitoring sheet of consumables use (94.2%). There is a statistically significant difference between the length of hospital stay, the quality of health education consultation notes, and the quality of nursing records recording between internal clinical departments (P
Keywords: Record keeping, nursing records, internal medicine.